GERAKAN SALAFI DI LOMBOK - Faizah Faizah (Harmoni, 2012)
The school of Salafi understands Islam teachings literary and limiting of intellectual role. Salafi can’t accept other religious understanding beside theirs, as described by Sasak people. The Sasak is an indigenious ethnic in Lombok. There are three culture mixed in that Island, Hinduism of Javanese old Kingdom, Islam and Balinese Hinduism. Some of the Sasak`s undertansding of theologic and ritual are parts of their culture or custome, such as human lifecycle, starting from birth, untill death. Salafi believes those traditions as bid`ah and opposite with Islam. The phenomena make tension in interaction among the peole and possibly become conflict.